PENGARUH NAA DAN BAP TERHADAP PERTUMBUHAN SUBKULTUR ANGGREK HASIL PERSILANGAN Dendrobium biggibum X Dendrobium liniale - Hartati, Sri; Budiyono, Agus; Cahyono, Ongko (Caraka Tani: Journal of Sustainable Agriculture, 2016)
Indonesia has a high diversity of species of orchids. One of them is the Dendrobium orchid. Orchid seeds do not have endosperm should be grown in a medium that has enough nutrients. Orchid propagation in vitro is strongly influenced by the composition of the medium used. Research through experiments aimed at studying the effect of NAA, BAP, NAA and BAP combination of the subculture plantlets growth of  hybrids orchid Dendrobium biggibum X liniale in Vacin Went media. Research conducted at the Laboratory of Tissue Culture Center for Plant Conservation Bogor Botanical Gardens. The experimental design used was completely randomized design (CRD) with two factors. The first factor was the concentration of Naphthalene Acetic Acid /NAA ( 0 ppm, 1 ppm, 3 ppm and 5 ppm). The second factor  was the type media of Benzyl Amino Purine /BAP ( 0 ppm, 1 ppm, 3 ppm and 5 ppm). Each treatment was replicated eight times. Analysis of the data by F test level 5% and if there is a significant difference continued with Duncan Multiple (Duncan's Multiple Range Test) level of 5%. The result showed that the addition  of NAA 3 ppm as much as 4,96 cm  and BAP 3 ppm as much as 4,41 cm  give a significant effect on the increase of high plantlets and  so NAA 3 ppm as much as 5,76 cm  effect  on  roots length , but did not significantly effect the number of leaves and roots.